A combinatorial model of malware diffusion via bluetooth connections. - Stefano Merler; Giuseppe Jurman (PLoS ONE, 2013)
We outline here the mathematical expression of a diffusion model for cellphones malware transmitted through Bluetooth channels. In particular, we provide the deterministic formula underlying the proposed infection model, in its equivalent recursive (simple but computationally heavy) and closed form (more complex but efficiently computable) expression.